Developing Vietnamese University Lecturers through Promoting Satisfaction - Khanh, Tran Thi Bao (Journal of Ecohumanism, 2024)
Lecturers are the core human resources of universities - directly performing the task of training human resources for society. Therefore, developing lecturers is of great significance, determining the strategic development of universities. Universities often implement the main measure to develop lecturers, which is to train to improve the qualifications and capacity of lecturers. However, in reality, there are many other measures to develop lecturers and this study deals with measures to promote lecturer satisfaction so that lecturers can be creative, actively teach, research and contribute to the success of the university. The author conducts an overview of the study and establishes two main contents/factors to promote lecturer satisfaction, including the factor "Income" and the factor "Development opportunities"; conducts a survey of 500 lecturers, including 250 lecturers at public universities and 250 lecturers at non-public universities in Vietnam. The results of the research and survey show that public university lecturers are more concerned with the factor “Promotion opportunities”, while non-public university lecturers are more concerned with the factor “Income”. From the results of this research, the author discusses policy issues to promote lecturers’ satisfaction with the two types of universities in Vietnam.